Who is staying home and who is not? Demographic, socioeconomic, and geographic differences in time spent outside the home during the COVID-19 outbreak in Japan - Tomoya Hanibuchi; Naoto Yabe; Tomoki Nakaya (Preventive Medicine Reports, 2021)
Studies have reported that many people changed their going-out behavior in response to the declaration of a state of emergency related to the coronavirus disease 2019 (COVID-19) in Japan. However, individual attributes of those who tended to stay home have not been examined. Therefore, this study examined the demographic, socioeconomic, and geographic characteristics of people who refrained from going out both before and after a state of emergency was declared. Using data from a nationwide online survey, this study retrospectively investigated the relative amount of time spent outside the home between mid-February and mid-May 2020. Multilevel linear regression analysis was performed to examine the association of time outside with demographic, socioeconomic, and geographic characteristics, and with the anxiety related to going out, in each period. Overall, respondents significantly reduced their time spent outside during the study period, especially after a state of emergency was declared. Those who were young, female, living with two or more people, had lower income, were not working, used public transportation, had chronic disease, and lived in large metropolitan areas were more likely to reduce time outside during a part of the study period. However, no significant differences were observed for occupational class, education, and neighborhood population density. Thus, the results showed a reduction in time outside during the COVID-19 outbreak and the existence of demographic, socioeconomic, and geographic differences in going-out behavior. Socioeconomic disparities and neighborhood differences in going-out behavior, and their influence on health should be continuously monitored.